Looking for the origins of the human brain: The role of South Africa in the history of palaeoneurology - Amélie Beaudet; Edwin de Jager; Mirriam Tawane; Brendon Billings (South African Journal of Science)
In 1925, Raymond Arthur Dart published his description and interpretations of the ‘Taung Child’ in the journal Nature, including a description of the natural brain endocast associated with the face and mandible. Details preserved in the endocast of the Taung Child have opened critical questions and debates about how the human brain evolved, and how to identify and study evidence of brain changes from fossil hominin crania. In this paper, we review and synthesise methodological innovations (how do we study fossil hominin brains?) and critical conceptual shifts (how did the hominin brain evolve?) triggered by the discovery of the Taung Child. In particular, we detail the impact of the study of the well-preserved crania and natural endocasts from the southern African hominin-bearing sites on our understanding of brain evolution and the integration of newly developed analytical tools into research in palaeoneurology (e.g. imaging techniques, 3D modelling). Additionally, we examine how the use of digital replicas of fossil hominin endocasts and the need to study extant human brains to form a comparative platform might raise questions about research practices (e.g. study and exhibition of fossil and extant human brains) and management of such invaluable heritage resources (e.g. data sharing). We finally consider how our view of human brain evolution, and in particular the putative uniqueness of the hominin brain, has changed over the last century.